The quality of online answers to parents who suspect that their child has an Autism Spectrum Disorder - Ben-Sasson, Ayelet; Pelleg, Dan; Yom-Tov, Elad (AAAI, 2016)
The growing diagnosis and public awareness of Autism Spectrum Disorders (ASD) leads more parents to seek answers to their suspicions for ASD in their child on Internet forums. This study describes an analysis of the quality of content of 371 answers on Yahoo Answers (YA), a social question and answer forum, to parents querying whether their child has ASD. We contrasted the perceived quality of answers by clinicians with that of parents. The study tested the feasibility of automatically assisting parents in selecting answers with higher quality using a predictive model based on the text of answers and the attributes of answerers.